Embedding sustainable development goals (SDGs) in an undergraduate business capstone subject using an experiential learning approach: A qualitative analysis. Issue 1 (March 2023) - Fang, Jim; O'Toole, Jacqueline
Abstract: Universities have an important role in ensuring that business school graduates can address issues regarding sustainable development and the achievement of the UN Sustainable Development Goals (SDGs) by 2030. While business schools have been progressively growing understanding of the SDGs, many have an unclear conception of their importance to business or how to effectively embed them into their curriculum. This paper explores the outcomes of one university in applying the SDGs as a learning framework for understanding global sustainability. Qualitative methodology was used to explore student perceptions regarding the efficacy of industry collaboration and Experiential Education Project-based Learning (EEPBL) methods, to integrate learning of SDGs into a university course. Through thematic analysis of 375 reflective essays and 18 semi-structured interviews, students reported an enhanced awareness and knowledge of SDGs, acquisition of key employability skills and development of new global perspectives. They found value in industry collaboration and EEPBL for acquiring a comprehensive understanding of the SDGs in a business context, and many developed an appreciation of their own agency for sustainability action in the future. This research can be presented as an example of one approach to both teaching students about the SDGs and embedding sustainability into their business curriculum. Highlights: Students reported enhanced awareness and knowledge of SDGs, acquisition of key employability skills and development of new global perspectives. A guide for business educators in teaching university students about the SDGs and embedding its learning into the business curriculum.